Rethinking emerging forces 60 years after the Bandung conference : Building Sovereignty, Preventing Hegemony - (:unkn) unknown (My University, 2015)
It is a report of an International and Multidisciplinary Conference in the framework of a commemoration of the 60th anniversary of the 1955 Bandung Asian-African Conference that took place in Jakarta, Bandung and Jakarta on October 27-31, 2015. The conference was organised in plenary and parallel seminars under transversal themes HISTORY and GENDER, five sectorial themes following the five pillars of sustainable development: CULTURE, ECOLOGY, ECONOMY, POLITICS AND SPIRITUALITY & RELIGION, and two special sessions due to the urgency of the case: PALESTINE and ROHINGYA. The conference involved 83 speakers and chairs coming from 33 countries: Australia, Austria, Brazil, Burkina Faso, Canada, Chile, China, Egypt, France, Gambia, Germany, Ghana, Hong Kong China, India, Indonesia, Japan, Malaysia, Morocco, Myanmar, Nepal, Netherlands, Nigeria, Palestine, Philippines, Russia, Senegal, Sudan, Switzerland, Thailand, United Kingdom, Uruguay, United States of America, Zimbabwe. This report includes the concept, programme, speeches, abstracts, list of participants and photos of the conference and its related events. A4, 100 pages of text and photos.
Keywords: African Research